Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the radius of the circle from the given equation:
[tex]\[ x^2 + y^2 + 8x - 6y + 21 = 0 \][/tex]
we need to rewrite the equation in the standard form of a circle's equation, [tex]\((x-h)^2 + (y-k)^2 = r^2\)[/tex]. We achieve this by completing the square for both [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
1. Start by grouping the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms together and move the constant to the other side:
[tex]\[ (x^2 + 8x) + (y^2 - 6y) = -21 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms. To do this, take half of the coefficient of [tex]\(x\)[/tex], square it, and then add and subtract this value inside the parentheses:
The coefficient of [tex]\(x\)[/tex] is 8. Half of this is 4, and squaring it gives [tex]\(4^2 = 16\)[/tex]:
[tex]\[ x^2 + 8x = (x + 4)^2 - 16 \][/tex]
3. Similarly, complete the square for the [tex]\(y\)[/tex] terms. Take half of the coefficient of [tex]\(y\)[/tex], square it, and then add and subtract this value inside the parentheses:
The coefficient of [tex]\(y\)[/tex] is -6. Half of this is -3, and squaring it gives [tex]\((-3)^2 = 9\)[/tex]:
[tex]\[ y^2 - 6y = (y - 3)^2 - 9 \][/tex]
4. Substitute these completed squares back into the equation:
[tex]\[ (x + 4)^2 - 16 + (y - 3)^2 - 9 = -21 \][/tex]
5. Combine the constants on the right side of the equation:
[tex]\[ (x + 4)^2 - 16 + (y - 3)^2 - 9 = -21 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 - 25 = -21 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 = -21 + 25 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 = 4 \][/tex]
6. The standard form of a circle's equation is [tex]\((x - h)^2 + (y - k)^2 = r^2\)[/tex]. Here, [tex]\((h, k)\)[/tex] is the center and [tex]\(r\)[/tex] is the radius. Comparing [tex]\((x + 4)^2 + (y - 3)^2 = 4\)[/tex] with the standard form, we can see:
[tex]\[ r^2 = 4 \][/tex]
[tex]\[ r = \sqrt{4} = 2 \][/tex]
Thus, the radius of the circle is 2 units.
The correct answer is:
[tex]\[ \boxed{2 \text{ units}} \][/tex]
[tex]\[ x^2 + y^2 + 8x - 6y + 21 = 0 \][/tex]
we need to rewrite the equation in the standard form of a circle's equation, [tex]\((x-h)^2 + (y-k)^2 = r^2\)[/tex]. We achieve this by completing the square for both [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
1. Start by grouping the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms together and move the constant to the other side:
[tex]\[ (x^2 + 8x) + (y^2 - 6y) = -21 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms. To do this, take half of the coefficient of [tex]\(x\)[/tex], square it, and then add and subtract this value inside the parentheses:
The coefficient of [tex]\(x\)[/tex] is 8. Half of this is 4, and squaring it gives [tex]\(4^2 = 16\)[/tex]:
[tex]\[ x^2 + 8x = (x + 4)^2 - 16 \][/tex]
3. Similarly, complete the square for the [tex]\(y\)[/tex] terms. Take half of the coefficient of [tex]\(y\)[/tex], square it, and then add and subtract this value inside the parentheses:
The coefficient of [tex]\(y\)[/tex] is -6. Half of this is -3, and squaring it gives [tex]\((-3)^2 = 9\)[/tex]:
[tex]\[ y^2 - 6y = (y - 3)^2 - 9 \][/tex]
4. Substitute these completed squares back into the equation:
[tex]\[ (x + 4)^2 - 16 + (y - 3)^2 - 9 = -21 \][/tex]
5. Combine the constants on the right side of the equation:
[tex]\[ (x + 4)^2 - 16 + (y - 3)^2 - 9 = -21 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 - 25 = -21 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 = -21 + 25 \][/tex]
[tex]\[ (x + 4)^2 + (y - 3)^2 = 4 \][/tex]
6. The standard form of a circle's equation is [tex]\((x - h)^2 + (y - k)^2 = r^2\)[/tex]. Here, [tex]\((h, k)\)[/tex] is the center and [tex]\(r\)[/tex] is the radius. Comparing [tex]\((x + 4)^2 + (y - 3)^2 = 4\)[/tex] with the standard form, we can see:
[tex]\[ r^2 = 4 \][/tex]
[tex]\[ r = \sqrt{4} = 2 \][/tex]
Thus, the radius of the circle is 2 units.
The correct answer is:
[tex]\[ \boxed{2 \text{ units}} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.